Pendekatan Fusi dalam Pengadilan Islam Indonesia: Memadukan Prinsip-Prinsip Islam dengan Praktik Mediasi Keluarga Asia dalam Kasus Perceraian - Wirdyaningsih; Rini Maryam; Qurrata Ayuni; Raihanah Abdullah (AL-ISTINBATH : Jurnal Hukum Islam, 2026)
This study explores the role of mediators in Indonesia’s Islamic Courts, focusing on their unique integration of Islamic principles with Asian family mediation practices in divorce cases. Unlike the theoretical model of mediation, which emphasizes mediators as neutral facilitators without providing advice, mediators in Indonesia’s Islamic Courts adopt a distinctive approach. They incorporate Islamic values, often offering moral and religious guidance, while also drawing on Asian family-court traditions that prioritize familial harmony and community involvement. This study uses the qualitative framework to analyze divorce mediation approach in court and its dynamics in divorce cases. Moreover, observation and interview are methods that applied to get comprehensive picture in the mediation process such as the individual experiences of each party, the dynamics of the relationships between the parties and between the parties and the mediator, and the mediator's perspective on the case, the parties, and the resolution of the case. In-depth interviews were conducted with non-judge mediators and the disputing parties at the South Jakarta Religious Court.  This paper highlights how these mediators navigate cultural, religious, and legal dimensions to address divorce disputes. The findings reveal a fusion mediation model that challenges conventional Western approach  offering insights into culturally sensitive dispute resolution in Islamic legal contexts